Reducing Disparities and Enhancing Sustainability in Asian Pension Systems - Yves Guerard; Mukul Asher; Donghyun Park; Gemma B. Estrada (Asian Development Bank (ADB), 2012)
Population aging is a global phenomenon but what sets Asia apart is the sheer scale and speed of its aging. Pension systems will have to play a bigger role but in most Asian countries pension systems are still underdeveloped, fragmented, and poorly financed. Asian countries need to embark on systematic pension reform now to meet the challenge of delivering affordable, adequate, and sustainable economic security to their fast-growing elderly population.
hdl:11540/1275
Keywords: 330; Alternde Bevölkerung; Rentenfinanzierung; Nachhaltigkeit; Altersvorsorge; Asien